Pengaruh Rekrutmen Dan Pelatihan Manajemen Terhadap Kinerja Sumber Daya Manusia Di Pondok Pesantren Al-Hikam Malang - Maschanuddin, Muhammad Agil; Djaelani, Abdul Kodir; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to analyze the influence of recruitment and training on the performance of Human Resources (HR) administrators at the Al-Hikam Islamic boarding school. This research used a quantitative method with a survey approach involving 30 respondents consisting of administrators at the Islamic boarding school. Data was collected through a questionnaire that measured respondents' perceptions of the recruitment process and training they received, as well as their performance in carrying out their duties. The data analysis technique used is multiple linear regression to find out how much influence recruitment and training have on HR performance. The research results show that recruitment does not have a significant influence on the HR performance of administrators at the Al-Hikam Islamic boarding school. Meanwhile, training has a positive and significant influence on HR performance. This research concludes that Islamic boarding schools need to prioritize the development of relevant and sustainable training programs to improve the performance of administrators' human resources.  Keywords: Recruitment, Training, HR Performance, Islamic Boarding School, Management, Human Resources Management.